Busting the Bankers' Club : Finance for the Rest of Us. - Epstein, Gerald; ProQuest (firma) (Berkeley : University of California Press, 2024)
An eye-opening account of the failures of our financial system, the sources of its staying power, and the path to meaningful economic reform.   Bankers brought the global economic system to its knees in 2007 and nearly did the same in 2020. Both times, the US government bailed out the banks and left them in control. How can we end this cycle of trillion-dollar bailouts and make finance work for the rest of us? Busting the Bankers' Club confronts the powerful people and institutions that benefit from our broken financial system--and the struggle to create an alternative. Drawing from decades of research on the history, economics, and politics of banking, economist Gerald Epstein shows that any meaningful reform will require breaking up this club of politicians, economists, lawyers, and CEOs who sustain the status quo. Thankfully, there are thousands of activists, experts, and public officials who are working to do just that. Clear-eyed and hopeful, Busting the Bankers' Club centers the individuals and groups fighting for a financial system that will better serve the needs of the marginalized and support important transitions to a greener, fairer economy.
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgments -- Preface -- Abbreviations -- Section I: From Boring to Roaring Banking -- 1. The Jekyll and Hyde of Finance -- 2. Boring Banking and the "Golden Age" of Capitalism -- 3. Roaring Banking: The World the Bankers Made -- 4. Are Bankers Essential Workers? -- Section II: The Bankers' Club and the Power of Finance -- 5. The Anatomy of the Bankers' Club -- 6. Lobbyists and Politicians versus the Club Busters -- 7. The Federal Reserve: Chairman of the Club -- 8. Financial Regulators and Their Lawyers -- 9. Nonfinancials Flip: The Financialization of the CEOs -- 10. Bankers' Club Economics -- Section III: Finance for the Rest of Us -- 11. Financial Regulation for All -- 12. Banks without Bankers: Finance to Meet Social Needs -- 13. Busting the Bankers' Club and Restoring Democracy -- Appendix: The Bankers' Club Assault on the New Deal Regulatory Structure -- Notes -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books